Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

i am asked to rewrite $2ie^{i\pi}+i^3$ into $x+iy$ form. i just tried all what i know so far, but couldnot come to solution. i said: $2ie^{i\pi}+i^3=2ie^{i\pi}-i$ but further i am stuck really. i am really eager to learn how things like this work. i appreciate any help and attempt to help.

the more difficult problems i am facing, the more i am loving maths. this problem was the first problem in my exam today. it took me 20 minutes. no sign of success..

EDIT: sorry, i forgot $e$. now it is there

share|cite|improve this question
Use $i = e^{i \frac{\pi}{2}}$ to expand the powers of $i$, and then use Euler's formula. – copper.hat Feb 5 '13 at 22:32
@copper.hat, how can this be? can you please explain me with small proof? btw, i forgot $e$ in my question, now updated – doniyor Feb 5 '13 at 22:33
There is the famous equation $e^{\pi i}+1=0$ – Hagen von Eitzen Feb 5 '13 at 22:34
Are you familiar with $e^{i \theta} = \cos \theta + i \sin \theta$? – copper.hat Feb 5 '13 at 22:34
@copper.hat, oh yeah. now i see what you mean – doniyor Feb 5 '13 at 22:35
up vote 2 down vote accepted

Using the main branch for the logarithmic function

$$i^{\pi i}=e^{\pi i\operatorname{Log}(i)}=e^{\pi i\left(\log|i|+\frac{\pi i}{2}\right)}=e^{\pi i\frac{\pi i}{2}}=e^{-\frac{\pi^2}{2}}\Longrightarrow$$

$$2i^{\pi i}+i^3=2e^{-\frac{\pi^2}{2}}-i$$

Added: after a modification of the question by the OP (much simpler now):

$$2ie^{\pi i}+i^3=-2i-i=-3i$$

share|cite|improve this answer
Thanks, but i forgot $e$ then updated my question, can you please update your answer also? – doniyor Feb 5 '13 at 22:36

Use Euler's formula:

$$e^{ix} = cos(x) + i sin(x)$$.

Plug in $x = \pi$ and you could then move on.

share|cite|improve this answer
Thanks, yeah now i got – doniyor Feb 6 '13 at 22:16

$$2ie^{i\pi}+i^3$$ Recall that: $$e^{i\theta} = \cos\theta + i\sin\theta$$ Thus, $e^{i\pi} = -1$. Substituting: $$-2i+i^3$$ Continuing using basic properties of $i$: $$-2i-i$$ $$\boxed{-3i}$$

share|cite|improve this answer
Thanks anorton, great – doniyor Feb 6 '13 at 22:15

$$ 2ie^{i\pi} + i^3 $$ $$ 2ie^{i\pi} - i $$

Recall Euler's Identity:

$$ e^{i\pi} + 1 = 0$$ and so: $$ e^{i\pi} = -1 $$ $$ 2i \cdot -1 - i$$ $$ -2i - i $$ $$ \color{red}{-3i} $$

Alternatively, use Euler's Formula, that: $$ e^{ix} = \cos x + i \sin x $$ Using $x=\pi$: $$ e^{i\pi} = \cos \pi + i \sin \pi $$ $$ e^{i\pi} = -1 + 0i $$ $$ e^{i\pi} = -1 $$

And proceed as above.

share|cite|improve this answer
Georg, very nice. thanks in tons dude. – doniyor Feb 6 '13 at 22:15

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.